(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
هدفت الدراسة إلى الكشف عن مجالات الضغوط النفسية التي تواجه مرضى السكري والتعرف إلى استراتيجيات مواجهة الضغوط النفسية تبعاً للنمط وتبعًا لجنس المريض، أجريت على عينة قوامها (345) مريض سكري منهم (95) مريض سكري نمط أول و (250) مريض سكري نمط ثاني، وقد استخدمت الباحثة لهذا الغرض استبانة للضغوط النفسية (من إعداد الباحثة)، واستبانه لاستراتيجيات مواجهة الضغوط النفسية ( من إعداد الباحثة). وقد أظهرت النتائج أن المصابون بالسكري يتعرضون لضغوط متعلقة بالعلاج بالمرتبة الأولى، ثم الضغوط الجسدية، يليه الضغوط النفسية، وثم المالية ، ويليه الضغوط الأسرية، وأخيراً الضغوط الاجتماعية، كما وجد أن الاستراتيجيات المستخدمة من قبل مرضى السكري من النمط الأول هي الاستراتيجيات السلبية ، بينما استخدم مرضى السكري من النمط الثاني الاستراتيجيات الايجابية في مواجهة الضغوط النفسية. This study tries to show the areas of psychological pressures facing people with diabetes and identify strategies of coping with related stress, depending on the style and depending on the sex of the patient. The study is conducted on a sample of 345 patients 95 of whom are first type diabetes and 250 are diabetes type II,. To identify psychological pressure, the researcher designed a questionnaire; and she also designed another one to identify strategies of coping with stress . Results show that people with diabetes are under pressure regarding the treatment first, then physical pressure, followed by psychological pressure, then, followed by family pressure, and finally social pressures. Results also show that strategies used by diabetes type 1 are negative strategies, while type II diabetes are positive strategies.